Effect of materials on the noise of a water hydraulic pump used in submersible. (1st February 2017) - Wu, Defa; Liu, Yinshui; Li, Donglin; Zhao, Xufeng; Li, Chao
Abstract: Open-circle sea water hydraulics, utilizing surrounding water as a working medium, has become more and more popular in submersible. Axial piston pump with port valves is used frequently in the open-circle water hydraulic system. Port valve is one of the important parts in this type pump. However, there are few literatures about the effect of the port valves' materials on the noise characteristic of the water pump. In this study, the effect of materials on the noise of the pump was researched through experimental and theory simulation methods. The influences of three kinds of plastics (Polyetheretherketone (PEEK), Polytetrafluoroethylene (PTFE), Aliphatic polyamides (NYLON)) and one kind of anti-corrosion stainless steel (316 L) are compared. The noise of the pump with the different materials port valve seat ranges from high to low as the order: 316 L>NYLON>PEEK>PTFE. The differences would contribute to the collision between valve spool and seat, which is identified by the simulating results. The experimental results showed that the difference of noise between PEEK and PTFE is small. In addition, the lifespan and volumetric efficiency are also taken into considering. The PEEK is selected to use in the seawater pump for a large submersible. Highlights: Port valve is one of the important parts of piston pump. Effect of materials on the noise of the pump was studied. Noise of the pump ranges from high to low as the order: 316L>NYLON>PEEK>PTFE. Life span and volumetric efficiency are also taken into considering. The PEEK is selected to use in the seawater pump for a submersible.